Time-trend analysis of tuberculosis diagnosis in Shenzhen, China between 2011 and 2020 - Hong, Chuang-Yue; Wang, Fu-Lin; Zhang, You-Tong; Tao, Feng-Xi; Ji, Le-Cai; Lai, Pei-Xuan; Li, Ming-Zhen; Yang, Chong-Guang; Tan, Wei-Guo; Jiang, Qi (Frontiers in Public Health, 2023)
Objective: To describe the trend of tuberculosis diagnosis in the migrant city Shenzhen, China, and to analyze the risk factors for diagnosis delays. Methods: Demographic and clinical information of tuberculosis patients from 2011 to 2020 in Shenzhen were extracted. A bundle of measures to enhance TB diagnosis had been implemented since late 2017. We calculated the proportions of patients who underwent a patient delay (>30 days from syndrome onset to first care-seeking) or a hospital delay (> 14 days from first care-seeking to tuberculosis diagnosis). The multivariable logistic regression was used to analyze the risk factors of diagnosis delays. Results: During the study period, a total of 43,846 patients with active pulmonary tuberculosis were diagnosed and registered in Shenzhen. Averagely, the bacteriological positivity rate of the patients was 54.9%, and it increased from 38.6% in 2017 to 74.2% in 2020. Overall, 30.3% and 31.1% of patients had a patient delay and hospital delay, respectively. The molecular test significantly increased the bacteriological positivity and decreased the risk of hospital delay. Local residents had a higher risk of delays in both patient care-seeking and hospital diagnosis than migrants. Compared to passive case-finding, active case-finding significantly decreased the risk of patient delay by 5.47 (4.85-6.19) times. Conclusion: The bacteriological positivity rate of TB patients in Shenzhen increased significantly but the diagnosis delays were still serious, which may need more attention in the active case-finding of risk populations and optimization of molecular testing.